2019
DOI: 10.21608/jappmu.2019.40304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Grape Seeds on Productive Performance and Nutrients Utilization for Broiler Chicks during Fattening Period

Abstract: A total of 216 day old broiler chicks (Arbor Acers) were weighed and distributed into equal 4 experimental groups of three replicates for each to explore the effect of dietary grape seeds (0, 0.5, 1.0 and 1.5%) addition on growth parameters, nutrients utilization and carcass characteristics as well as economic efficiency during fattening period (1-35 days of age). The results indicated that live body weight, body weight gain , feed conversion ratio and production index traits significantly (P≤0.05) improved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the present study, grape byproducts incorporated less than 0.5 g/kg of tannins in all treatments. Previous studies [ 11 , 13 , 30 ] also showed that the individual dietary inclusion of 30 g/kg of GS or GK, resulting in an incorporation of less than 0.40 g/kg of tannins to the diet, had no detrimental effect on growth performance nor on ileal protein digestibility of chickens. However, when GS and GK are combined in the diet (for instance, with the dietary inclusion of grape pomace), a higher dietary concentration of tannins can be reached before impairing chicken performance.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, grape byproducts incorporated less than 0.5 g/kg of tannins in all treatments. Previous studies [ 11 , 13 , 30 ] also showed that the individual dietary inclusion of 30 g/kg of GS or GK, resulting in an incorporation of less than 0.40 g/kg of tannins to the diet, had no detrimental effect on growth performance nor on ileal protein digestibility of chickens. However, when GS and GK are combined in the diet (for instance, with the dietary inclusion of grape pomace), a higher dietary concentration of tannins can be reached before impairing chicken performance.…”
Section: Discussionmentioning
confidence: 95%